2007
DOI: 10.1111/j.1439-0272.2007.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neferine on cytosolic free calcium concentration in corpus cavernosum smooth muscle cells of rabbits

Abstract: To study the relaxation mechanisms of neferine (Nef) on the corpus cavernosum smooth muscle (CCSM), the CCSM cells from New Zealand White rabbits were cultured in vitro. [Ca(2+)](i) was measured by fluorescence ion digital imaging system (FIDIS), using Fluo-2/AM as a Ca(2+)-sensitive fluorescent indicator. Nef (0.1, 1 and 10 micromol l(-1)) had no effect on the resting [Ca(2+)](i) (P > 0.05). In the presence of extracellular Ca(2+) (2.5 mmol l(-1)), Nef (0.1, 1 and 10 micromol l(-1)) inhibited [Ca(2+)](i) elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Since changes in intracellular Ca 2+ levels can lead to the activation of NF-κB in LPS-stimulated macrophages (Zhou et al, 2006), and Neferine, Liensinine and Isoliensinine are inhibitors of Ca 2+ in ventricular myocytes and corpus cavernosum smooth muscle cells (Chen et al, 2007;Feng et al, 2002;Wang et al, 2000), the effects of Neferine, Liensinine and Isoliensinine on the level of cytosolic free Ca 2+ in LPS-activated RAW264.7 macrophages were investigated. Flow cytometry analysis showed that increased cytosolic free Ca 2+ level in LPS-stimulated macrophages was significantly inhibited by treatment with Figure 1.…”
Section: Effects Of Neferine Liensinine and Isoliensinine On Cytosmentioning
confidence: 99%
See 1 more Smart Citation
“…Since changes in intracellular Ca 2+ levels can lead to the activation of NF-κB in LPS-stimulated macrophages (Zhou et al, 2006), and Neferine, Liensinine and Isoliensinine are inhibitors of Ca 2+ in ventricular myocytes and corpus cavernosum smooth muscle cells (Chen et al, 2007;Feng et al, 2002;Wang et al, 2000), the effects of Neferine, Liensinine and Isoliensinine on the level of cytosolic free Ca 2+ in LPS-activated RAW264.7 macrophages were investigated. Flow cytometry analysis showed that increased cytosolic free Ca 2+ level in LPS-stimulated macrophages was significantly inhibited by treatment with Figure 1.…”
Section: Effects Of Neferine Liensinine and Isoliensinine On Cytosmentioning
confidence: 99%
“…However, the potential antiinflammatory targets of these three alkaloids in the upstream pathway of NF-κB are still unclear. Previous studies on various cell types have shown that bisbenzylisoquinoline alkaloids, such as Neferine, Liensinine, Isoliensinine, Dauricine, Tetrandrine, Cepharanthine and Berbamine, are inhibitors of Ca 2+ (Chen et al, 2007;Feng, Yu, & Xiao, 2002;Murakami, Okajima, & Uchiba, 2000;Qian, 2002;Ren et al, 2008;Wang, Nong, Yao, & Jiang, 2000). In addition, several bisbenzylisoquinoline alkaloids have been found to bind to CaM and inhibit the activity and expression of CaM (Hu, Chen, Hao, Huang, & Peng, 1989;Sun, Hu, & Xu, 1990;Xu & Zhang, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Because AD is highly associated with ChEs and BACE1 activities, inflammation, and oxidative stress, N. nucifera can be considered as a preventive measure to inhibit the progression of AD. Using different in vivo animal models, Jung et al demonstrated the requirement of anti-oxidant, antiinflammatory, and the inhibitory effects of neferine (Tomita et al, 1962;Kunitomo et al, 1973;Liu et al, 2006) 8 Norarmepavine Leaves, Seeds (Kupchan et al, 1963;Duan et al, 2014) 9 Bromo methyl armepavine Leaves, Seeds (Rai et al, 2006) 10 Methoxymethy lisoquinoline Leaves, Seeds (Rai et al, 2006) 11 Lotusine Embryo, Seeds, Fruit Wang et al, 1991) 12 Higenamine Plumule (Zhou et al, 2013) (Chao et al, 1962;Furukawa et al, 1965;Guo and Chen, 1984;Chen et al, 2007b;Furukawa, 1966) 19 Isoliensinine (Isolie) Seeds, Fruit, Embryo (Tomita et al, 1965;Chen et al, 2007b;Furukawa, 1966) 20 Neferine Seeds, Fruit, Embryo (Chen et al, 2007a;Zhou et al, 2013;Sugimoto et al, 2015;Zhang et al, 2015b;Furukawa, 1966) Fruits and seeds (Toyoda, 1966;Mukherjee et al, 1997aMukherjee et al, , 1997b 189Asparagine…”
Section: Pharmacological Reportsmentioning
confidence: 99%
“…The authors reported that neferine increased cAMP concentration in a dose-dependent manner (Chen et al, 2008). Neferine relaxes corpus caverosum smooth muscle cells by inhibiting calcium elevation in the cells via blocking voltage-dependent calcium channel, alpha 1 adrenoceceptor operated calcium channel, and calcium release from intracellular calcium pool (Chen et al, 2007a). Furthermore, Mutreja et al (Mutreja et al, 2008) found that hydroalcoholic extract of N. nucifera seeds has an anti-estrogenic effect without altering the general physiology of reproductive system.…”
mentioning
confidence: 99%
“…Because of the complex chemical ingredients, it remains unclear which ingredient exactly, and by which mechanisms, has a positive effect in treating ED. Recent studies have found that some extracts from traditional Chinese medicines, containing alkaloids, coumarin and saponin compounds, can relax the smooth muscle of corpus cavernosum [3][4][5][6][7][8][9][10][11][12][13][14][15], which provides an open window for developing new drugs for the treatment of ED.…”
Section: Introductionmentioning
confidence: 99%